“SELF-REGULATED LEARNING ANALYSIS IN THE COVID-19 PANDEMIC ERA” : META SYNTHESIS OF SELF REGULATED LEARNING ABILITIES - Rembulan Catra Banyu Biru; Mustofa Kamil; Sardin Sardin (IKIP Siliwangi Bandung, 2021)
This research was conducted to synthesize the ability of students to learn independently in the Covid-19 era which is based on four themes, namely: goal assistance (planning), self-improvement (monitoring), measuring themselves (controlling), and strengthening themselves (reflection). The research was conducted using the meta-synthesis method in four journals with various cases of students' independent learning abilities in the Covid-19 pandemic era. The results of the synthesis show that the self-regulated learning ability consists of: (1) assistance with goals (planning), namely the ability to make plans to sort priorities related to objectives, (2) increased self-interest (monitoring), namely the ability to check the extent of the project walking and progress in achieving goals, namely the ability to exercise self-control by giving attention to the process being undertaken, (4) self-improvement (reflection), namely the ability to look back at their performance and determine the similarity they feel, and the influence they feel. gained from their performance. The implications of these findings can be used as a reference for other researchers who want to change their self-regulated learning abilities.